El impacto del robo y el hurto en la economía doméstica: un estudio exploratorio sobre los datos de Lima Metropolitana - Mujica, Jaris; Zevallos, Nicolás; López, Noam; Prado, Bertha (Pontificia Universidad Católica del Perú. Fondo Editorial, 2015)
This research estimates the impact of robbery and theft in the household economies of the victims, according to their socioeconomic background. We analyze the current situation of Lima Metropolitana between 2011 and 2012, focusing on Cercado de Lima, a highly transited area where many people from different socioeconomic backgrounds converge. In this place, there is also a high rate and a high prevalence of robbery and theft. Based on a range of values involved in the average robbery and theft sustained in a standardized inventory of stolen goods, we estimate the percentage of the impact of the felony, such as the time of recovery of the goods that were substracted. This study allows us to conclude that the percentage of the impact of the felony and its recovery time are related to the socioeconomic strata, affecting mainly its lower levels.

La investigación propone un ejercicio de estimación del impacto del robo y hurto en la economía doméstica de las víctimas, según sus niveles socioeconómicos. Aborda la situación de Lima Metropolitana entre los años 2011 y 2012, concentrándose en el Cercado de Lima, zona de tránsito de personas de diversos estratos y que a su vez registra una alta tasa y prevalencia de robos y hurtos en la vía pública. Basados en un rango de valores involucrados en un robo y hurto promedio sostenido en un inventario estandarizado de bienes robados y hurtados, se estima tanto el porcentaje de impacto del hecho como el tiempo de recuperación de los bienes sustraídos. El estudio permite concluir que el porcentaje de impacto y el tiempo de recuperación, se dispone en función de los estratos socioeconómicos, afectando en mayor medida a los niveles inferiores.
The impact of robbery and theft in the household economy: An exploratory study on data from Lima Metropolitana
Keywords: Delito; Crimen; Robo; Hurto; Pobreza; Sociology; Felony; Crime; Robbery; Theft; Poverty; https://purl.org/pe-repo/ocde/ford#5.04.00